The Influence of the State Energy Policy on electricity market structure in the Czech Republic - Harant, Alexandr (2010)
The State Energy Policy, which belongs to the key topic of economic policy, basically aims to ensure long-term and stable energy supply; in the case of electricity creates conditions for self-reliant and strong market in context of the geopolitical position of the Czech Republic. There is an ongoing debate over the new version of approved concept which implements commitments arising from membership of the Czech Republic in the EU and consequently circulates State Energy Policy from 2004 on renewable sources and partly reviewing pririties of economic and political targets. The main objective of bachelor thesis will be an analysis of the impact of strategic decisions in th field of electricity energy, especially decision about ČEZ Group, a.s. which was determined as the strongest producer and saler of electricity in Czech Republic. This paper will try to compare visions of energy strategy of neighboring countries and evaluace the current status of dominant companies in czech energy market.